Advancing green recovery: Integrating one health in sustainable wildlife management in the Asia-Pacific Indigenous People and Local Communities - Nareerat Sangkachai; Anuwat Wiratsudakul; Delia G. Randolph; Maxine Whittaker; Acty George; Martin R. Nielsen; Nicholas Hogarth; Dirk U. Pfeiffer; Carsten Smith-Hall; P.O. Nameer; Latiffah Hassan; Gautam Talukdar; et al. (One Health)
Wildlife (in this paper: wild animals) deliver a crucial range of ecosystem services on human health and livelihood, particularly in Indigenous People and Local Communities (IPLCs). ‘One Health’ extends beyond just health; it also includes a comprehensive framework that can address wildlife and biodiversity conservation to enhance the well-being of humans, animals, and the environment with multisectoral collaboration. Therefore, integrating One Health principles into wildlife management was suggested in this review to improve the quality of life by reducing poverty, improving food security, and preventing zoonotic diseases in IPLCs. The relationship between wildlife interactions and the emergence of pathogens that can be transmitted between wild animals, domestic and production animals, and humans underscores the need to incorporate a One Health approach to mitigate risk. This integration will also contribute to conserving wild animals and their habitats and biodiversity for ecosystem balance. This review highlights the importance of One Health in supporting sustainable wildlife management to achieve a green recovery through policies and actions based on global and national regulatory frameworks, development of local policies with community engagement, risk assessment and communication, sustainable wildlife use practices, and conducting research and innovation. Monitoring and analyzing data on supply chains and economic values can serve as a decision-support tool for sustainability wildlife management. A theory of change for sustainable wildlife management and enhancing human well-being is proposed using the One Health approach. All these activities must respect local cultures and traditions, ensuring that One Health and community-based approaches effectively benefit local communities.